SLFN11 inhibits checkpoint maintenance and homologous recombination repair - Mu, Yanhua; Lou, Jiangman; Srivastava, Mrinal; Zhao, Bin; Feng, Xin-hua; Liu, Ting; Chen, Junjie; Huang, Jun (EMBO reports, 2016)
High expression levels of SLFN11 correlate with the sensitivity of human cancer cells to DNA‐damaging agents. However, little is known about the underlying mechanism. Here, we show that SLFN11 interacts directly with RPA1 and is recruited to sites of DNA damage in an RPA1‐dependent manner. Furthermore, we establish that SLFN11 inhibits checkpoint maintenance and homologous recombination repair by promoting the destabilization of the RPA–ssDNA complex, thereby sensitizing cancer cell lines expressing high endogenous levels of SLFN11 to DNA‐damaging agents. Finally, we demonstrate that the RPA1‐binding ability of SLFN11 is required for its function in the DNA damage response. Our findings not only provide novel insight into the molecular mechanisms underlying the drug sensitivity of cancer cell lines expressing SLFN11 at high levels, but also suggest that SLFN11 expression can serve as a biomarker to predict responses to DNA‐damaging therapeutic agents. Synopsis High levels of SLFN11 sensitize cancer cell lines to DNA‐damaging agents by inhibiting checkpoint maintenance and homologous recombination repair. SLFN11 expression might serve as a biomarker to predict responses to DNA‐damaging therapeutic agents. SLFN11 is a DNA damage responsive protein and forms a complex with RPA. SLFN11 inhibits checkpoint maintenance and homologous recombination repair by destabilizing the RPA–ssDNA complex. The role of SLFN11 in sensitizing cancer cells to DNA‐damaging agents depends on a physical protein–protein interaction between SLFN11 and RPA1. Graphical Abstract High levels of SLFN11 sensitize cancer cell lines to DNA‐damaging agents by inhibiting checkpoint maintenance and homologous recombination repair. SLFN11 expression might serve as a biomarker to predict responses to DNA‐damaging therapeutic agents.